Teachers'challenges in teaching reading to English first Additional Language learners : a case study of Seshego High School - Moswane, Andries Pududu (My University, 2019)
The purpose of this study was to explore the challenges encountered by teachers in teaching reading to EFAL learners in rural schools. This is based on the fact that reading is a fundamental skill upon which all formal education depends. In view of this, a child who does not learn reading early enough is doom to underperform in their academic pursuits. Thus, any child who doesn’t learn to read early and well would not easily master the other literacy skills and is unlikely to ever perform well in school or in life. However, teaching reading to English first additional language learners comes with a lot of challenges. To this effect, Sentsho (2000) argues that many teachers are not perfect in that regard and this imperfectness impacts negatively on the outcomes which is on the learners (child). If the teachers are incapable of using basic structures correctly, or if his/her pronunciation is so bad that the words are incomprehensible, he/she would not be able to teach the spoken language competently. Among the main challenges identified in the literature review, the lack of teaching skills, remuneration, lack of resources, overcrowded classrooms are the major challenges encountered by the teachers. The study is located in the interpretive paradigm which sought to explore teachers’ experiences and their views. The experiences and the qualifications of teachers were taken into consideration during the empirical study when the interviews, seminar and the observations were conducted. Qualitative research approach was adopted in the study with the intentions of finding as much detail as possible using a case study design. Participants for this study were teachers who teach English first additional language at rural schools in the Seshego Circuit in Polokwane, Limpopo. The empirical investigation revealed that teachers did not have necessary skills and expertise to teach reading to EFAL learners. They knew less about the approaches to teaching reading and that reading was treated as a separate entity from speaking and writing. The conditions that they found themselves were appalling due to lack of motivation and support from the Department of Education, overcrowding in classrooms, lack of resources, socio-economic status etc. and how these factors impact negatively on the teaching of reading. Also important to note was the fact that the teachers did not receive any form of in-service training at their respective schools in relation to the teaching of reading. The investigation concluded that the teachers were qualified and had enough experience in teaching English but not reading per se.
Thesis (Ph.D.(Language Education)) -- University of Limpopo, 2019
Keywords: Reading; Teachers; Literacy skill; Teaching skill; Active learning; Teaching; English language -- Study and teaching (Secondary)